The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1159/000492031
|View full text |Cite
|
Sign up to set email alerts
|

Breathing Hydrogen-Oxygen Mixture Decreases Inspiratory Effort in Patients with Tracheal Stenosis

Abstract: Background: Hydrogen-oxygen mixture (H2-O2) may reduce airway resistance in patients with acute severe tracheal stenosis, yet data supporting the clinical use of H2-O2 are insufficient. Objectives: To evaluate the efficacy and safety of breathing H2-O2 in acute severe tracheal stenosis. Methods: Thirty-five consecutive patients with severe acute tracheal stenosis were recruited in this prospective self-control study. Air, H2-O2 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 29 publications
5
25
0
Order By: Relevance
“…Previous researches have demonstrated 67% H 2 and 33% O 2 mixture gas strikingly decreased ROS induced by ischemia-reperfusion in the brain [34, 50], liver [51], and heart [52] in animal models. Clinical studies have reported 67% H 2 and 33% O 2 mixture reduced the inspiratory effort in patients with acute severe tracheal stenosis [53] and restored the exhausted supply of CD8+ T cells in patients with advanced colorectal cancer [54]. Our results showed 67% H 2 and 33% O 2 mixture gas increased T-SOD and GSH activity and decreased MDA content against the elevated ROS level induced by CIH.…”
Section: Discussionsupporting
confidence: 60%
“…Previous researches have demonstrated 67% H 2 and 33% O 2 mixture gas strikingly decreased ROS induced by ischemia-reperfusion in the brain [34, 50], liver [51], and heart [52] in animal models. Clinical studies have reported 67% H 2 and 33% O 2 mixture reduced the inspiratory effort in patients with acute severe tracheal stenosis [53] and restored the exhausted supply of CD8+ T cells in patients with advanced colorectal cancer [54]. Our results showed 67% H 2 and 33% O 2 mixture gas increased T-SOD and GSH activity and decreased MDA content against the elevated ROS level induced by CIH.…”
Section: Discussionsupporting
confidence: 60%
“…Furthermore, breathing H 2 -O 2 might reduce the inspiratory effort in patients with acute severe tracheal stenosis and can be used safely for this purpose (Zhou et al, 2019). Although H 2 gas is flammable, concentrations < 4%, together with oxygen at room temperature, are incombustible.…”
Section: Safety Of Hydrogenmentioning
confidence: 99%
“…Clinical research has shown that hydrogen dissolved in irrigation solution reduces corneal endothelial damage during phacoemulsification ( Igarashi et al, 2019 ). Furthermore, breathing H 2 -O 2 might reduce the inspiratory effort in patients with acute severe tracheal stenosis and can be used safely for this purpose ( Zhou et al, 2019 ). Although H 2 gas is flammable, concentrations < 4%, together with oxygen at room temperature, are incombustible.…”
Section: Safety Of Hydrogenmentioning
confidence: 99%
“…Patients with COVID-19 have been characterized by increasingly laborious breathing as a result of greater airway resistance. Due to smaller molecular weight, helium-oxygen mixed gas has been applied to ameliorate dyspnea in patients with respiratory failure [102] and chronic obstructive pulmonary disease [103] . However, due to the low cost-effectiveness ratio, helium–oxygen mixed gas has not been extensively adopted in clinical practice.…”
Section: Advances In Clinical Managementmentioning
confidence: 99%